Tenofovir alafenamide for prevention and treatment of hepatitis B virus reactivation and de novo hepatitis. Issue 9 (19th August 2021) - Inada, Kento; Kaneko, Shun; Kurosaki, Masayuki; Yamashita, Koji; Kirino, Sakura; Osawa, Leona; Hayakawa, Yuka; Sekiguchi, Shuhei; Higuchi, Mayu; Takaura, Kenta; Maeyashiki, Chiaki; Tamaki, Nobuharu; et al.
Abstract: Background and Aim: Administration of tenofovir alafenamide (TAF) as prevention or treatment of hepatitis B virus (HBV) reactivation is not well known. The aim of this study is to reveal the efficacy and safety of TAF against HBV reactivation. Methods: Entecavir (ETV) and TAF were given to 66 and 11 patients, respectively, as prophylaxis against or treatment of HBV reactivation during chemotherapy or immune suppression therapy from January 2010 to June 2020. The antiviral effects and safety were assessed. Results: At week 24, the antiviral effects on patients receiving ETV and TAF were similar in terms of reduction of HBV DNA (−2.83 ± 1.45log IU/mL vs −3.05 ± 2.47log IU/mL; P  = 0.857) and achieving undetectable levels of HBV DNA (78.8 vs 90.9%; P  = 0.681). There was no significant difference in the decrease in the estimated glomerular filtration rate (eGFR) between the two groups (−0.62 ± 11.2 mL/min/1.73 m 2 vs −3.67 ± 13.2 mL/min/1.73 m 2 ; P  = 0.291). Conclusion: TAF is safe and effective against HBV reactivation. Abstract : The aim of this study is to reveal the efficacy and safety of tenofovir alafenamide (TAF) as prophylaxis against or treatment of hepatitis B virus (HBV) reactivation. The antiviral effects in terms of HBV DNA reduction on patients receiving entecavir and TAF were similar, and there was no significant difference in renal dysfunction between both groups. TAF is safe and effective against HBV reactivation.